A population-based investigation of the association between alcohol intake and serum total ghrelin concentrations among cigarette-smoking, non-alcohol-dependent male individuals. (1st September 2021) - Farokhnia, Mehdi; Murphy, Gwen; Weinstein, Stephanie J.; Shah, Navan N.; Parisi, Dominick; Albanes, Demetrius; Leggio, Lorenzo
Highlights: Ghrelin is involved in the neurobiology of alcohol use and is being studied as a pharmacotherapeutic target. Effects of alcohol intake in different settings, populations, and time frames on the ghrelin system are not well understood. In this study, higher circulating total ghrelin levels were found among alcohol drinkers than non-drinkers. No quantitative association was found between the amount of daily alcohol intake and blood total ghrelin concentrations. Abstract: Background: Ghrelin plays significant roles in regulating appetite, food intake, and metabolism. Furthermore, the ghrelin system is increasingly being studied in relation to alcohol seeking behaviors. To this end, it is important to understand the possible effects of alcohol intake on the ghrelin system. The aim of the present study was to investigate the association between alcohol drinking and circulating ghrelin levels in a large sample of cigarette-smoking, non-alcohol-dependent male individuals. Methods: We utilized data from two nested case-control studies (study A, n = 807; study B, n = 976) based within the Alpha-Tocopherol, Beta-Carotene Cancer Prevention (ATBC) trial. Data on alcohol consumption (grams of pure alcohol consumed per day) were obtained via a food frequency questionnaire. Blood samples were also collected (after 12 h of fasting), and serum concentrations of total ghrelin were measured by radioimmunoassay. Results: Dichotomous comparison between alcohol drinkers (>0 g/day of alcohol intake) and non-drinkers (0 g/day of alcohol intake) found higher total ghrelin levels among individuals who drank alcohol than those who did not, with statistically significant results in study A [ F (1, 798) = 4.32, P = 0.03] and less robust results in study B [ F (1, 966) = 2.62, P = 0.10], controlling for a list of factors that may influence ghrelin levels and/or differ between drinkers and non-drinkers. Bivariate correlational analysis among drinkers found no association between the quantity of daily alcohol intake and blood total ghrelin concentrations. Conclusion: These results indicate elevated ghrelin levels among alcohol drinkers and provide additional/relevant information on the complex interaction between alcohol use and the ghrelin system.